The ASMC seeder improves maize sowing in the western region of Burkina Faso - Barro, Albert; Millogo, Vinsoun; Dao, Begue; Sayaogo, Boureima; Amoussou, Toundji Olivier; Kéré, Michel; Burdick, Robert; Harrigan, Timothy; Srivastava, Ajit (International Journal of Environment, Agriculture and Biotechnology, 2022)
In Burkina Faso, cultivation operations (tillage, sowing, weeding, fertilization, etc.) are mainly carried out by women and young people. Among them, sowing is a particular constraint that determines the success or failure of production. In this country, maize is grown by 78% of producers in the rainy season. In order to improve production, a simple seeder that can be made by local craftsmen was designed as part of the Appropriate Scale Mechanization Consortium (ASMC) project and evaluated with SR21 maize seed in the Koumbia region. It has been harnessed by two oxen. The equipment is evaluated on a plowed plot and on minimum tillage plot. Seed dimensions and distribution disc characteristics were measured. The characteristics of sowing, the traction force and the labor times were measured and compared with those of manual sowing. The results indicate that the sowing time is 3.6 to 3.8 h ha-1, i.e., 8 to 10 times faster than manual practice. The traction force is 22.6 kgf (226 N). That is available for oxen hitch even with one animal. Seed calibration can improve tool performance. The tool has great potential for increasing production if the other production inputs are assured.